THE EFFECTS OF TWO KINDS OF AGRICULTURAL WASTES (WHEAT AND BARELY STRAWS) ON NRC% OF ASPEN PARTICLEBOARDS - Mohammad ali Podinehpoor (Regional Information Center for Science and Technology (RICeST), 2006)
In this investigation, the influences of two kinds of agricultural wastes (wheat and barely straws) mixed with Aspen particles were studied for use as insulation boards. Barely and wheat straws were chosen because of their availability. The manufacturing parameters were: a specific gravity of 0.2, 0.4 and 0.6 gr/cm3, and residual agriculture contents (0/1 00, 10/90, 20/80 and 30/70 weight of residual agriculture/ wood particle) of 0, 10, 20 and 30wt%. A commercial urea-fonnaldehyde adhesive was used as composite binder. Sound absorption coefficients were measured at five frequencies (250, 500, 1000, 2000, and 4000 hertz).The results showed when frequencies increased, sound absorption increased until it reaches to 2000 hertz but in 4000 hertz, sound absorption decreased. Between manufacturing parameters, kind of straws didn't have significant influence on noise reduction coefficient. The best density for absorb waves under 1000 in hertz was 0.4 gr/cm3 with 30% of straws but for waves with frequency higher than 1000 in hertz the best density was 0.2 gr/cm3 with 30% of straws.